Partial pressure (or fugacity) of carbon dioxide, salinity and other variables collected from underway - surface observations using Carbon dioxide (CO2) gas analyzer, Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement and other instruments from the EXPLORER OF THE SEAS in the Caribbean Sea, Gulf of Mexico and North Atlantic Ocean from 2002-03-02 to 2002-12-28 (NCEI Accession 0108131) ... - Wanninkhof, Rik; Huss, Betty E.; Castle, Robert D. (NOAA National Centers for Environmental Information, 2013)
This dataset includes biological, chemical, meteorological, physical and underway - surface data collected from EXPLORER OF THE SEAS in the Caribbean Sea, Gulf of Mexico and North Atlantic Ocean from 2002-03-02 to 2002-12-28 and retrieved during cruise EX0209 - EX0251. These data include BAROMETRIC PRESSURE, FLUORESCENCE, Partial pressure (or fugacity) of carbon dioxide, SALINITY, SEA SURFACE TEMPERATURE, WIND DIRECTION and WIND SPEED. The instruments used to collect these data include Carbon dioxide (CO2) gas analyzer and Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement. These data were collected by Rik Wanninkhof of NOAA Atlantic Oceanographic and Meteorological Laboratory (AOML) as part of the VOS Explorer of the Seas Lines 2002 dataset. ...